2008
DOI: 10.1007/s00276-008-0390-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the sphenopalatine foramen and its arterial content

Abstract: The sphenopalatine artery is the end artery of the maxillary artery located within the pterygopalatine fossa and passes through the sphenopalatine foramen (SPF) on lateral nasal wall. Nasal bleeding from this artery is potentially life threatening and may urgently require endonasal endoscopic occlusion. The aims of the present study have been first to investigate the location of the SPF, secondly the pattern of the main branches of the sphenopalatine artery at the foramen. 12 adult dry skulls and 6 adult cadav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 12 publications
3
42
1
Order By: Relevance
“…The average outer diameter of the PLNA obtained in this study was smaller than that reported by Prades et al (1.80 ± 0.20 mm) [24], which can be explained by the small sample in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…The average outer diameter of the PLNA obtained in this study was smaller than that reported by Prades et al (1.80 ± 0.20 mm) [24], which can be explained by the small sample in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…In majority of the cases (72%), the infraorbital foramen was situated in the narrow range of 55.1to 65 mm distance from ANS (Table 2). 5 worked on bony skull, whereas we studied on cadaveric specimens, which is more close to real-life situations. Another posteriorly situated reference that can assist in localization of foramen is horizontal lamina of IT.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior nasal spine (ANS), horizontal plate of palatine bone, and bony crista ethmoidalis are few such examples. 1,4,5 Large variations with regard to the measurements of distance of SPF from the landmarks have been reported in the literature. 5 The current study was planned to provide a detailed account of the variations of the SPF and to determine the location of SPF by taking measurements from anteriorly and posteriorly located intranasal landmarks relevant to endoscopic localization of SPA and the best angle for endoscope elevation to reach the SPF.…”
Section: Introductionmentioning
confidence: 99%
“…The sphenopalatine artery, which arrives via the sphenopalatine foramen, is the most important of these vessels [8]. The greater palatine artery enters in the nose by the incisive foramen.…”
Section: Discussionmentioning
confidence: 99%